2002
DOI: 10.1152/ajpheart.00924.2001
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE contributes to the acute fall in cerebral blood flow after subarachnoid hemorrhage in the rat

Abstract: man. 20-HETE contributes to the acute fall in cerebral blood flow after subarachnoid hemorrhage in the rat. Am J Physiol Heart Circ Physiol 282: H1556-H1565, 2002. First published December 6, 2001 10.1152/ajpheart.00924.2001.-This study examined the effects of blocking the formation of 20-hydroxyeicosatetraenoic acid (20-HETE) on the acute fall in cerebral blood flow after subarachnoid hemorrhage (SAH) in the rat. In vehicle-treated rats, regional cerebral blood flow (rCBF) measured with laser-Doppler flowmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 43 publications
5
88
2
Order By: Relevance
“…We selected a dose of 10 mg/kg administered intraperitoneally, which produced 1 h concentrations (Kehl et al, 2002). However, the brain concentrations reported in the study by Kehl et al were 7.2 mmol/L as compared with 0.2 mmol/L reported in the present study.…”
Section: Discussioncontrasting
confidence: 61%
“…We selected a dose of 10 mg/kg administered intraperitoneally, which produced 1 h concentrations (Kehl et al, 2002). However, the brain concentrations reported in the study by Kehl et al were 7.2 mmol/L as compared with 0.2 mmol/L reported in the present study.…”
Section: Discussioncontrasting
confidence: 61%
“…An increase in 20-HETE has been documented to be associated with exacerbation of MI and stroke in multiple animal models, and inhibition of the production of 20-HETE decreases the infarct size and ablates strokes in several animal models (34)(35)(36)(37). To study the mechanism by which 20-HETE enhances the speed of blood clotting, we measured the function of coagulation and platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the levels of 20-HETE increase in the CSF of rats (Kehl et al, 2002;Cambj-Sapunar et al, 2003), dogs (Hacein-Bey et al, 2004a), and man (Hacein-Bey et al, 2004b) following SAH and inhibition of the synthesis of 20-HETE, with 17-ODYA or HET0016 (Kehl et al, 2002;Cambj-Sapunar et al, 2003), or blockade of its vasoconstrictor actions with WIT0002 (Yu et al, 2004) can prevent the acute fall in CBF. There is also evidence that blockade of the synthesis of 20-HETE can even reverse delayed vasospasm in dogs subjected to the dual hemorrhage model (Hacein-Bey et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…and thiobutabarbital (Inactin; 50 mg/kg i.p.) and surgically prepared for induction of SAH and measurement of CBF through an intact cranial window as previously described (Kehl et al, 2002;Cambj-Sapunar et al, 2003). The head of the rat was placed in a stereotaxic apparatus and the atlantooccipital membrane was exposed by separating the muscle layers at the base of the skull.…”
Section: Effects Of Pretreatment Of Rats With Ts-011 On the Acute Falmentioning
confidence: 99%
See 1 more Smart Citation